The role of nanoscale heterogeneous structure in simultaneously enhancing strength and ductility of high-oxygen Ti–6Al–4V alloy. (15th March 2021) - Luo, Yifei; Zhang, Zhen; Xie, Yuehuang; Liang, Jiamiao; Zhang, Deliang
ABSTRACT: A high-oxygen (∼0.5 wt-%) Ti–6Al–4V alloy with a nanoscale heterogeneous structure consisting of ultrathin-lamellar-structured and coarse-grained domains was fabricated by powder processing and thermomechanical consolidation. In investigating the effect of heat treatment on this alloy, it was found that changing such nanoscale heterogeneous structure into a regular α / β lamellar structure, which was commonly produced in conventional fabrication routes, caused not only a significant decrease of strength but also a clear drop in tensile ductility. Analysis revealed that the intrinsic plasticity of coarse-grained domains and deformation coordination across domain boundaries captured microcracks and increased strain hardening rate, leading to the enhanced ductility of heterogeneous structure. In contrast, the intergranular fracture mode and inadequate variation of crystallographic orientations of α lamellae were ductility-deterioration mechanisms for the regular lamellar structure.